2016
DOI: 10.1002/mnfr.201500796
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin A, C, and D, but not iso‐urolithin A and urolithin B, attenuate triglyceride accumulation in human cultures of adipocytes and hepatocytes

Abstract: Taken together, our results demonstrated that UroA, UroC, and UroD, but not isoUroA and UroB, reduce TG accumulation and increase FA oxidation in adipocytes as well as hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 48 publications
7
74
0
Order By: Relevance
“…In this context, we recently showed that urolithins are able to reduce the pro-inflammatory response to high glucose levels in cultured neonatal cardiomyocytes and fibroblasts [13], suggesting that they can prevent the diabetes-induced microenvironmental changes triggering myocardial inflammation and functional impairment in the diabetic heart. These findings confirmed previous in vitro studies demonstrating the positive role of urolithin supplementation in different cell models, including anti-inflammatory activity in endothelial cells and macrophages [15, 3236] and beneficial effects on lipid metabolism in adipocytes and hepatocytes [37]. However, the biological effects of in vivo urolithin administration in the setting of diabetes, as well as in other pathological conditions, remain to be characterized [38].…”
Section: Discussionsupporting
confidence: 87%
“…In this context, we recently showed that urolithins are able to reduce the pro-inflammatory response to high glucose levels in cultured neonatal cardiomyocytes and fibroblasts [13], suggesting that they can prevent the diabetes-induced microenvironmental changes triggering myocardial inflammation and functional impairment in the diabetic heart. These findings confirmed previous in vitro studies demonstrating the positive role of urolithin supplementation in different cell models, including anti-inflammatory activity in endothelial cells and macrophages [15, 3236] and beneficial effects on lipid metabolism in adipocytes and hepatocytes [37]. However, the biological effects of in vivo urolithin administration in the setting of diabetes, as well as in other pathological conditions, remain to be characterized [38].…”
Section: Discussionsupporting
confidence: 87%
“…Previously, we demonstrated that UroA decreased TG accumulation in human hepatocytes . To determine whether UroA injection recapitulates these results in vivo , we investigated hepatic TG regulation.…”
Section: Resultsmentioning
confidence: 93%
“…Our laboratory has previously demonstrated the role of UroA in reducing lipogenesis by using primary cultures of human adipocytes in vitro . In this study, we collected eWAT from mice to validate the physiological function of UroA in adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…In a series of gut microbiota‐mediated reactions, ellagitannins are hydrolysed yielding ellagic acid, which is converted to urolithins through the loss of one of its two lactones and by successive removal of hydroxyl groups (Espín et al, ). This process leads to the production of urolithin A, urolithin B, urolithin C, and urolithin D. Urolithins have been shown to regulate cellular processes involved in normal and pathological conditions (Espín et al, ; Kang, Kim, Tomás‐Barberán, Espín, & Chung, ; Tang et al, ). A few recent studies have also reported that administration and consumption of these colonic metabolites, in particular urolithin A, promote positive health outcomes in animal models (Ryu et al, ; Savi et al, ; Tang et al, ).…”
Section: Discussionmentioning
confidence: 99%